Hydrothermal carbon high-dispersion supported copper catalyst as well as preparation method and application thereof

Through the preparation of hydrothermal carbon high-dispersion supported copper catalyst, the oxygen-containing functional groups of biomass during the hydrothermal process improve the dispersion and stability of copper, the problem of poor antibiotic degradation effect in traditional methods is solved, and efficient antibiotics are achieved Degradation and recyclability of catalysts.

CN119236932APending Publication Date: 2025-01-03HUBEI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411361445.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art is difficult to effectively degrade antibiotic pollution in water. Traditional biological treatment methods have poor effect on antibiotic biotoxicity treatment. The metal loaded transition metal catalyst prepared by high-temperature calcination method is low and easy to agglomerate, resulting in a reduction in catalytic activity and stability.

Method used

The preparation method of hydrothermal carbon-high dispersion-supported copper catalyst is adopted. The hydrothermal carbonization method of plant biomass and copper nitrate in alkaline aqueous solution is used to form highly dispersed Cu0 and Cu2O loads, which improves the activation of hydrogen peroxide and the reactive oxygen species. Produce and enhance the degradation ability of antibiotics.

Benefits of technology

It achieves efficient degradation and conversion of antibiotics, and the catalyst has excellent catalytic activity and stability, is suitable for large-scale industrial generation, and can be recycled and used in multiple cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236932A_ABST
    Figure CN119236932A_ABST
Patent Text Reader

Abstract

The invention provides a hydrothermal carbon high-dispersion supported copper catalyst as well as a preparation method and application thereof, and relates to the technical field of catalysts. Plant biomass is used as a carbon source, copper nitrate is used as a copper source, an alkaline aqueous solution is used for adjusting the pH value, copper is loaded on hydrothermal carbon through a hydrothermal carbonization method, and the hydrothermal carbon high-dispersion loaded copper catalyst is obtained. And activating hydrogen peroxide to catalytically degrade the antibiotic wastewater by using the product as a catalyst. The supported copper catalyst is prepared by adopting a hydrothermal method, the dispersity and stability of copper on the surface of the supported copper catalyst are improved by utilizing a large number of oxygen-containing functional groups on plant biomass in the hydrothermal process, and a metal component in a reduction state is obtained by utilizing the reducibility of persistent free radicals in the hydrothermal carbon forming process; activation of hydrogen peroxide and generation of active oxygen species are improved, and efficient degradation and safe conversion of antibiotics are further improved. In addition, waste is selected as a carrier raw material, waste is turned into wealth, the preparation method is cheap and easy to obtain, the preparation process is simple, and the method is suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of catalyst technology, and in particular to a hydrothermal carbon highly dispersed copper-loaded catalyst and a preparation method and application thereof. Background Art

[0002] Antibiotics pose a threat to ecosystems and human health due to their biological toxicity, and antibiotics in water urgently need to be safely disposed of. Currently, commonly used treatment technologies include physical, biological and chemical methods. Physical methods (such as nanofiltration, adsorption, etc.) can only separate antibiotics from water, which still require further treatment and cannot fundamentally solve the problem of antibiotic pollution. Because antibiotics are biologically toxic to microorganisms, traditional biological treatment methods are difficult to effectively degrade them.

[0003] In response to the organic pollution problem caused by new pollutants such as antibiotics in water, the heterogeneous Fenton technology has been a research hotspot in the field of advanced oxidation technology because of its strong oxidation ability and no secondary pollution in the decomposition of hydrogen peroxide. However, bulk transition metals and their oxides have the problem of high ion dissolution leading to secondary pollution. Supported transition metal catalysts can not only reduce the amount of transition metals used, but also stabilize the metal components. The choice of carrier is extremely critical. It is necessary not only to control the cost of the carrier, but also to simplify the preparation process.

[0004] Biochar is a new type of carbon-based material made from waste biomass. It is widely available and low-cost. It has been extensively studied because of its rich pore structure and surface active groups. Preparation methods include high-temperature pyrolysis and hydrothermal carbonization. At present, more research focuses on the preparation of metal-loaded biochar by high-temperature calcination, but the prepared loaded transition metal catalyst has a low metal loading and is very easy to agglomerate, reducing the catalytic activity and catalyst stability. However, reports on the preparation of loaded transition metal catalysts by hydrothermal carbonization are relatively rare. Summary of the invention

[0005] The purpose of the present application is to provide a hydrothermal carbon highly dispersed copper-loaded catalyst, which has low cost and has high efficiency in degradation and conversion of antibiotics in wastewater.

[0006] Another object of the present application is to provide a method for preparing a hydrothermal carbon highly dispersed loaded copper catalyst, which is simple and convenient and suitable for large-scale industrial production.

[0007] Another object of the present application is to provide a hydrothermal carbon highly dispersed loaded copper catalyst for use in catalytic degradation treatment of antibiotic wastewater, which has excellent catalytic activity and can be recycled.

[0008] In order to solve the above technical problems, the technical solution adopted in this application is:

[0009] On the one hand, the present application provides a method for preparing a highly dispersed copper catalyst loaded on hydrothermal carbon, the preparation method comprising: using plant biomass as a carbon source and copper nitrate as a copper source, adjusting the pH value with an alkaline aqueous solution, and loading copper on the hydrothermal carbon by a hydrothermal carbonization method to obtain a highly dispersed copper catalyst loaded on hydrothermal carbon.

[0010] On the other hand, the present application provides a hydrothermal carbon highly dispersed copper catalyst prepared by the above method.

[0011] On the other hand, the present application provides the use of the above-mentioned hydrothermal carbon highly dispersed copper catalyst in catalytic degradation treatment of antibiotic wastewater.

[0012] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:

[0013] 1. This application adopts a hydrothermal method to prepare a supported copper catalyst, selects plant waste as a carrier precursor, and utilizes a large number of oxygen-containing functional groups on biomass during the hydrothermal process to improve the dispersion and stability of copper on its surface. This is different from the traditional calcination method, which is that metals form metal oxides and aggregate under high temperature conditions, and are often loaded in the form of metal oxide blocks. In addition, this application utilizes the reducibility of persistent free radicals in the hydrothermal carbon formation process to obtain a reduced metal component (Cu 0 and Cu2O), improve the activation of hydrogen peroxide and the generation of reactive oxygen species, and further improve the efficient degradation and safe conversion of antibiotics. In addition, the use of waste as carrier raw materials turns waste into treasure, is cheap and easy to obtain, and has a simple preparation process, which is suitable for large-scale industrial production.

[0014] 2. The highly dispersed copper-loaded hydrothermal carbon catalyst prepared by the present invention exhibits excellent catalytic activity in the system of degrading ofloxacin with activated hydrogen peroxide, and can be recycled and reused multiple times. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 X-ray diffraction (XRD) patterns of different samples in Examples 1-3;

[0017] Figure 2 High magnification transmission electron microscopy (HRTEM) images of samples prepared in Example 2 and Example 3;

[0018] Figure 3The degradation curves of ofloxacin by different catalysts in Example 4 are shown;

[0019] Figure 4 This is the dissolution diagram of the metal copper ion in the process of catalytic degradation of ofloxacin of the sample prepared in Example 4;

[0020] Figure 5 This is the 4-cycle degradation curve of ofloxacin by the Cu@BC catalyst in Example 4. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0022] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to specific embodiments.

[0023] A method for preparing a hydrothermal carbon highly dispersed copper-loaded catalyst, the preparation method comprising: using plant biomass as a carbon source and copper nitrate as a copper source, adjusting the pH value with an alkaline aqueous solution, and loading copper on the hydrothermal carbon by a hydrothermal carbonization method to obtain a hydrothermal carbon highly dispersed copper-loaded catalyst.

[0024] In some embodiments of the present application, the above preparation method specifically comprises the following steps:

[0025] S1. Dissolve Cu(NO3)2·3H2O in water, then add plant biomass while stirring, and disperse by ultrasonic to form a uniform solution; and add it dropwise into an alkaline aqueous solution while stirring, add ethylene glycol after the precipitate is dispersed, and continue stirring to obtain a suspension;

[0026] S2, transferring the suspension to perform a hydrothermal reaction;

[0027] S3, washing, drying and grinding the product after the reaction in step S2 to obtain a hydrothermal carbon highly dispersed copper-loaded catalyst.

[0028] In some embodiments of the present application, the stirring speed in the above step S1 is 1200 rpm; the ultrasonic dispersion is specifically to form a uniform solution by ultrasonic dispersion in a 60KHz ultrasonic cleaning machine for 15 minutes.

[0029] In some embodiments of the present application, the plant biomass in the above-mentioned step S1 includes at least one of bean stalks, straws, orange peels, sawdust and corn cobs; the concentration of the alkaline aqueous solution is 0.5-2.0 mol / L, and the alkaline aqueous solution includes a NaOH aqueous solution or a KOH aqueous solution.

[0030] In some embodiments of the present application, the mass ratio of Cu(NO3)2·3H2O to plant biomass in the above-mentioned step S1 is (0.4-1):1, when the alkaline aqueous solution is a NaOH aqueous solution, the mass ratio of Cu(NO3)2·3H2O to NaOH is (0.12-1):1, when the alkaline aqueous solution is a KOH aqueous solution, the mass ratio of Cu(NO3)2·3H2O to KOH is (0.09-0.7):1; the mass ratio of Cu(NO3)2·3H2O to ethylene glycol is (0.01-0.09):1.

[0031] In some embodiments of the present application, the hydrothermal reaction is carried out in a sealed high-pressure reactor lined with polytetrafluoroethylene, and the temperature of the hydrothermal reaction is 170-190° C. and the time is 4-36 hours.

[0032] In some embodiments of the present application, the cleaning in the above step S3 is specifically washing with ethanol and deionized water alternately until neutral; the drying temperature is 60-80°C and the time is 8-12h.

[0033] A hydrothermal carbon highly dispersed copper-loaded catalyst is prepared by the method.

[0034] Application of a hydrothermal carbon highly dispersed copper catalyst in catalytic degradation treatment of antibiotic wastewater.

[0035] In some embodiments of the present application, the above-mentioned antibiotics include ofloxacin, ciprofloxacin, sulfamethoxazole and tetracycline hydrochloride.

[0036] In some embodiments of the present application, the above-mentioned catalytic degradation treatment method is: dispersing 10-50 mg of hydrothermal carbon highly dispersed copper catalyst into a wastewater solution containing antibiotics, and after 30-120 minutes to reach adsorption-desorption equilibrium, adding 0.01-0.05 mol / L hydrogen peroxide for degradation.

[0037] The features and properties of the present application are further described in detail below in conjunction with the examples. It should be noted that the experimental methods used in the following examples are conventional methods unless otherwise specified, and the materials, reagents and instruments used therein, unless otherwise specified, can be purchased through commercial channels. All reagents used are analytically pure. Milli-Q high-purity water (18.2ΜΩ) was used during the experiment.

[0038] Example 1

[0039] In this example, a hydrothermal carbon highly dispersed copper catalyst (Cu@BC) is prepared, and the steps are as follows:

[0040] 0.12g Cu(NO3)2·3H2O was completely dissolved in 12.5mL ultrapure water, and then 0.25g bean stalks were added under vigorous stirring at 1200rpm, and dispersed in a 60KHz ultrasonic cleaning machine for 15min to form a uniform solution, and then added dropwise to a 1.2M NaOH solution under stirring, and 2.5mL ethylene glycol was added after the precipitate was dispersed, and continued to stir vigorously for 30min; then, the suspension was transferred to a 50mL polytetrafluoroethylene-lined autoclave, sealed and reacted at 180°C for 24h; the product after the reaction was alternately washed with ethanol and deionized water until neutral, dried at 60°C for 12h, and finally the dried sample was ground to obtain a hydrothermal carbon-supported copper catalyst, that is, 9% Cu@BC in this embodiment;

[0041] Example 2

[0042] In this embodiment, a highly dispersed copper catalyst (Cu@BC) loaded on hot water carbon is prepared, and the steps are as follows:

[0043] 0.24 g of Cu(NO3)2·3H2O was completely dissolved in 12.5 mL of ultrapure water, and then 0.25 g of bean stalks was added under vigorous stirring. The solution was dispersed by ultrasonication in a 60 kHz ultrasonic cleaning machine for 15 min to form a uniform solution, and then added dropwise to a 1.2 M NaOH solution under stirring. After the precipitate was dispersed, 2.5 mL of ethylene glycol was added, and vigorous stirring was continued for 30 min. Subsequently, the suspension was transferred to a 50 mL polytetrafluoroethylene-lined autoclave, sealed, and reacted at 180°C for 24 h. The product after the reaction was alternately washed with ethanol and deionized water until neutral, dried at 60°C for 12 h, and finally the dried sample was ground to obtain a hydrothermal carbon-loaded copper catalyst, namely, the 13% Cu@BC of this embodiment.

[0044] Example 3

[0045] In this example, a hydrothermal carbon catalyst (BC) is prepared, and the steps are as follows:

[0046] 0.25 g of bean stalks were added to 12.5 mL of ultrapure water, and dispersed in a 60 KHz ultrasonic cleaning machine for 15 min to form a uniform solution, and then added dropwise to a 1.2 M NaOH solution under stirring. After the precipitate was dispersed, 2.5 mL of ethylene glycol was added, and the solution was stirred vigorously for 30 min. Subsequently, the suspension was transferred to a 50 mL polytetrafluoroethylene-lined autoclave, sealed, and reacted at 180° C. for 24 h. The product after the reaction was alternately washed with ethanol and deionized water until neutral, dried at 60° C. for 12 h, and finally the dried sample was ground to obtain the BC of this embodiment.

[0047] X-ray diffraction phase analysis was performed on the bean stalk, the hydrothermal carbon (BC) prepared in Example 3, the 9% Cu@BC prepared in Example 1, and the 13% Cu@BC prepared in Example 2. The results are as follows: Figure 1 As shown, from Figure 1 It can be seen that the products Cu@BC with different copper loadings all retain the characteristic diffraction peaks of hydrothermal carbon. The characteristic diffraction peaks at 2θ of 15.5° and 22.5° are the (101) and (002) diffraction planes of the cellulose microcrystalline structure, and the Cu@BC@BC@BC@43.3°, 50.5°, and 74.2° are the Cu@BC@BC@43.3°, Cu@BC@50.5°, and Cu@BC@60. 0 The diffraction peaks of Cu2O (JCPDS 74-1230) appear at 36.4° and 61.3°, indicating that the Cu in Cu@BC is mainly in the form of Cu 0 and Cu2O in the form of supported on hydrothermal carbon.

[0048] The high magnification transmission electron microscopy (HRTEM) images of the BC (without copper loading) prepared in Example 3 and the 13% Cu@BC catalyst prepared in Example 2 are shown in FIG. Figure 2 As shown, Figure 2 The left is BC, Figure 2 The right is 13% Cu@BC. Figure 2 It can be seen that the prepared BC catalyst has an amorphous structure, and the 13% Cu@BC catalyst is highly dispersed and loaded with a large number of Cu nanoparticles with a size of about 2 nm.

[0049] Example 4

[0050] This example tests the catalytic performance of the highly dispersed copper catalyst loaded on hydrothermal carbon; the method is as follows: 10 mg of the 13% Cu@BC catalyst prepared in Example 2 is dispersed into 100 mL of 10 mg / L ofloxacin (OFX) solution, and after 30 min of adsorption-desorption equilibrium, 0.04 mol / L hydrogen peroxide (H2O2) is added to start the degradation reaction. At each given time interval, 2 mL of the solution is taken and 1.5 mL of the filtrate is collected with a 0.22 μm filter, and then 0.1 M Na2S2O3 is added to quench the oxidation reaction. OFX concentration is analyzed by high performance liquid chromatography (HPLC, Thermo Fisher Scientific, UltiMate 3000) equipped with a UV / vis detector. Separation is carried out on a C18 column, the mobile phase consists of 76% phosphoric acid aqueous solution (pH = 2.6) and 24% acetonitrile, the flow rate is 0.8 mL / min, the injection volume is 20 μL, the column temperature is maintained at 25 ° C, and the detection wavelength is 288 nm.

[0051] This embodiment sets up different control experiments, wherein in control experiment 1, 13% Cu@BC catalyst is not added, and the other steps are the same; in control experiment 2, BC catalyst is used to replace 13% Cu@BC catalyst; in control experiment 3, hydrogen peroxide is not added.

[0052] At the end of each experiment, the catalyst was filtered, washed, and dried in an oven at 60°C, and stability and repeatability experiments were then carried out under the same catalytic conditions.

[0053] From the Lamber-Beer law, it can be known that the concentration of ofloxacin solution is proportional to the size of its absorption peak area at the characteristic absorption wavelength. Therefore, the catalytic degradation rate can be quantitatively analyzed by detecting the change in the absorption peak area of ​​the solution during the degradation process, and then the catalytic effect of the catalyst can be measured by the degradation rate (R).

[0054] R=[(A0-A) / A0]×100%

[0055] Where A0 is the absorption peak area before adding hydrogen peroxide; A is the absorption peak area at degradation time t.

[0056] Figure 3The degradation kinetics of ofloxacin by the above-mentioned different catalysts can be seen from the figure. It can be seen that H2O2 alone has almost no removal effect on ofloxacin. After reaching the adsorption-desorption equilibrium at 30 minutes, when there is only the carrier (BC), the degradation of ofloxacin by the catalyst is not significantly improved after adding H2O2, indicating that the carrier does not play a catalytic oxidation role on ofloxacin. The adsorption efficiency of 13% Cu@BC alone on ofloxacin is 32%, while in the presence of H2O2, the degradation efficiency of 13% Cu@BC on ofloxacin is increased to 86% within 120 minutes. It can be seen that the highly dispersed loading of copper can indeed improve the degradation of the catalyst ofloxacin.

[0057] Figure 4 This is the dissolution diagram of copper ions during the degradation of ofloxacin by the above-mentioned 13% Cu@BC catalyst. It can be seen from the figure that the solubility of metallic copper ions in the solution of the 13% Cu@BC catalyst is 0.64 mg / L when the degradation is 10 minutes. The dissolution value tends to be stable at 120 minutes, reaching 0.93 mg / L, which is lower than the copper emission limit (1.0 mg / L) in the national "Sanitary Standard for Drinking Water" (GB 5749-2022), and will not cause secondary pollution.

[0058] Figure 5 This is a graph showing the degradation curve of ofloxacin by the 13% Cu@BC catalyst after four cycles. It can be seen from the graph that after four cycles, the degradation efficiency of ofloxacin can still reach more than 86%, showing good reusability.

[0059] In summary, the hydrothermal carbon highly dispersed copper-loaded catalyst and its preparation method and application in the embodiment of the present application have the following advantages:

[0060] 1. This application adopts a hydrothermal method to prepare a supported copper catalyst, selects plant waste as a carrier precursor, and utilizes a large number of oxygen-containing functional groups on biomass during the hydrothermal process to improve the dispersion and stability of copper on its surface. This is different from the traditional calcination method, which is that metals form metal oxides and aggregate under high temperature conditions, and are often loaded in the form of metal oxide blocks. In addition, this application utilizes the reducibility of persistent free radicals in the hydrothermal carbon formation process to obtain a reduced metal component (Cu 0 and Cu2O), improve the activation of hydrogen peroxide and the generation of reactive oxygen species, and further improve the efficient degradation and safe conversion of antibiotics. In addition, the use of waste as carrier raw materials turns waste into treasure, is cheap and easy to obtain, and has a simple preparation process, which is suitable for large-scale industrial production.

[0061] 2. The highly dispersed copper-loaded hydrothermal carbon catalyst prepared by the present invention exhibits excellent catalytic activity in the system of degrading ofloxacin with activated hydrogen peroxide, and can be recycled and reused multiple times.

[0062] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present application.

Claims

1. A method for preparing a highly dispersed copper catalyst loaded on hydrothermal carbon, characterized in that: The preparation method comprises the following steps: using plant biomass as a carbon source and copper nitrate as a copper source, adjusting the pH value with an alkaline aqueous solution, and loading copper on hydrothermal carbon by a hydrothermal carbonization method to obtain a hydrothermal carbon highly dispersed copper-loaded catalyst.

2. The method for preparing a hydrothermal carbon highly dispersed copper catalyst according to claim 1, characterized in that: The preparation method specifically comprises the following steps: S1. Dissolve Cu(NO3)2·3H2O in water, then add plant biomass while stirring, and disperse by ultrasonic to form a uniform solution; and add it dropwise into an alkaline aqueous solution while stirring, add ethylene glycol after the precipitate is dispersed, and continue stirring to obtain a suspension; S2, transferring the suspension to perform a hydrothermal reaction; S3. The product after the reaction in step S2 is washed, dried and ground to obtain a hydrothermal carbon highly dispersed copper-loaded catalyst.

3. The method for preparing a hydrothermal carbon highly dispersed copper catalyst according to claim 2, characterized in that: The plant biomass in step S1 includes at least one of bean stalks, straws, orange peels, sawdust and corn cobs; the concentration of the alkaline aqueous solution is 0.5-2.0 mol / L, and the alkaline aqueous solution includes a NaOH aqueous solution or a KOH aqueous solution.

4. The method for preparing a hydrothermal carbon highly dispersed copper catalyst according to claim 3, characterized in that: In the S1 step, the mass ratio of Cu(NO3)2·3H2O to plant biomass is (0.4-1):1, the mass ratio of Cu(NO3)2·3H2O to NaOH is (0.12-1):1 or the mass ratio of Cu(NO3)2·3H2O to KOH is (0.09-0.7):1; the mass ratio of Cu(NO3)2·3H2O to ethylene glycol is (0.01-0.09):

1.

5. The method for preparing a hydrothermal carbon highly dispersed copper catalyst according to claim 2, characterized in that: The hydrothermal reaction is carried out in a sealed high-pressure reactor lined with polytetrafluoroethylene. The temperature of the hydrothermal reaction is 170-190° C. and the time of the hydrothermal reaction is 4-36 hours.

6. The method for preparing a hydrothermal carbon highly dispersed copper catalyst according to claim 2, characterized in that: The cleaning in step S3 is specifically washing with ethanol and deionized water alternately until neutral; the drying temperature is 60-80° C. and the drying time is 8-12 hours.

7. A hydrothermal carbon highly dispersed copper catalyst, characterized in that: It is prepared by the method according to any one of claims 1 to 6.

8. Use of the hydrothermal carbon highly dispersed copper catalyst as claimed in claim 7 in catalytic degradation treatment of antibiotic wastewater.

9. The use of a hydrothermal carbon highly dispersed copper catalyst in catalytic degradation treatment of antibiotic wastewater according to claim 8, characterized in that: The antibiotics include ofloxacin, ciprofloxacin, sulfamethoxazole and tetracycline hydrochloride.

10. The use of a hydrothermal carbon highly dispersed copper catalyst in catalytic degradation treatment of antibiotic wastewater according to claim 8, characterized in that: The catalytic degradation treatment method is as follows: dispersing a hydrothermal carbon highly dispersed copper catalyst into a wastewater solution containing antibiotics, and after reaching adsorption-desorption equilibrium after 30-120 minutes, adding hydrogen peroxide for degradation.